Implementation of Regional Sukuk (Islamic bonds) as a solution for Regional economic development in Indonesia - Nurfahmi Islami Kaffah; Wirdyaningsih Wirdyaningsih (Proceedings of AICS - Social Sciences, 2019)
This research is a juridical and empirical study about the implementation of Regional Sukuk (Islamic bonds) in Indonesia.  Sukuk constitute the Islamic bonds that are issued as proof of ownership of assets or infrastructure projects both in rupiah and foreign currency based on sharia principles. sukuk represents one of the strategic sources of state infrastructure financing in addition to state bonds (SUN). The impact of the strengthening of regional autonomy in Indonesia has triggered regional demands that sukuk not only be issued by central government authorities but also by provincial governments. Regulatory, the implementation of regional sukuk has not been supported by the legal basis of the law governing the mechanism and regulation of regional Sukuk. However, as a form of commitment to regional autonomy and equitable development, the Government through the Financial Services Authority (OJK) has established a Regulation on the Issuance of Regional Sukuk in 2017. This study discusses the regulatory aspects of regional sukuk, sharia principle in the operation sukuk, mechanism for issuing sukuk regions, the stakeholders, and the benefits of implementing regional sukuk. The Regional Sukuk Law regulation represents highly necessitate by the regional governments anda communities. Regional Sukuk can encourage the growth of sharia industries in the region, encourage clean infrastructure project governance based on sharia, alternative investment in local communities, and can increase the local revenue capacity.